Research Advances in Gametogenesis and Embryogenesis Using Pluripotent Stem Cells - Luo, Yuxin; Yu, Yang (Frontiers in Cell and Developmental Biology, 2022)
The previous studies of human gametogenesis and embryogenesis have left many unanswered questions, which hinders the understanding of the physiology of these two vital processes and the development of diagnosis and treatment strategies for related diseases. Although many results have been obtained from animal studies, particularly mouse research, the results cannot be fully applied to humans due to species differences in physiology and pathology. However, due to ethical and material limitations, the direct study of human gametes and embryos is very difficult. The emergence and rapid development of organoids allow the construction of organoid systems that simulate gametogenesis and embryogenesis in vitro, and many studies have successfully established organoid systems for some parts of or even the entire processes of gametogenesis and embryogenesis. These studies typically start with the establishment of mouse models and then modify these models to obtain human organoid models. These organoid models can be used to obtain a better understanding of the signaling pathways, molecular mechanisms, genetics, and epigenetic changes involved in gametogenesis and embryogenesis and could also be applied to clinical applications, such as drug screening. Here, we discuss the formation of primordial stem cell-like cells (PGCLCs), and in vitro-induced gametes and embryoids using pluripotent stem cells (PSCs). We also analyze their applications and limitations.